Antimicrobial Terpenes Suppressed the Infection Process of Phytophthora in Fennel-Pepper Intercropping System - Yang, Yuxin; Li, Ying; Mei, Xinyue; Yang, Min; Huang, Huichuan; Du, Fei; Wu, Jiaqing; He, Yiyi; Sun, Junwei; Wang, Haining; He, Xiahong; Zhu, Shusheng; et al. (Frontiers in Plant Science, 2022)
Biodiversity cultivation is widely used in agricultural ecosystems for yield increase and disease control. Here, a greenhouse experiment confirmed the intercropping between fennel and pepper to control Phytophthora capsici blight disease. Experimentally, the roots and root exudates of fennel can effectively interfere with the infection stages of P. capsici at the soil concentration by attracting zoospores and inhibiting the motility of the zoospores and germination of the cystospores. Five terpene compounds (D-limonene, estragole, anethole, gamma-terpenes, and beta-myrcene) that were identified in the fennel rhizosphere soil and root exudates were found to interfere with P. capsica infection. D-Limonene was associated with positive chemotaxis with zoospores, and the mixture of five terpene compounds showed a strong synergistic effect on infection process of P. capsici, especially for zoospores rupture. Furthermore, reactive oxygen species (ROS) accumulation induced by the five terpene compounds in the hyphae was evaluated using a fluorescent probe. ROS accumulation may be one of the antimicrobial mechanisms of terpene compounds. Above all, we proposed that terpene compounds secreted from fennel root play a key role in Phytophthora disease suppression in this intercropping system, and the intercropping model provides a new reference for the spatial layout based on biodiversity theory.